2021
DOI: 10.1242/dev.199493
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific control of convergent differentiation by a Forkhead repressor

Abstract: During convergent differentiation, multiple developmental lineages produce a highly similar or identical cell type. However, few molecular players that drive convergent differentiation are known. Here, we show that the C. elegans Forkhead transcription factor UNC-130 is required in only one of three convergent lineages that produce the same glial cell type. UNC-130 acts transiently as a repressor in progenitors and newly-born terminal cells to allow the proper specification of cells related by lineage rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Thus, as in vertebrates, C. elegans possesses glia of both neuroectodermal and mesodermal origin. Some genes affecting C. elegans neuroepithelial glia development have been characterized [12][13][14][15] ; however, virtually nothing is known about GLR glia development or functions. GLR glia extend intricate, non-overlapping sheet-like processes that ensheath the inner aspect of the C. elegans brain neuropil (the nerve ring; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as in vertebrates, C. elegans possesses glia of both neuroectodermal and mesodermal origin. Some genes affecting C. elegans neuroepithelial glia development have been characterized [12][13][14][15] ; however, virtually nothing is known about GLR glia development or functions. GLR glia extend intricate, non-overlapping sheet-like processes that ensheath the inner aspect of the C. elegans brain neuropil (the nerve ring; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that unc-130 is required to make a difference between AWA and ASG, chemosensory neurons generated from the ABp(l/r)aapap lineage from which AIB is derived 30 . unc-130 specifies two glial types that arise from the neighboring lineage (ABp(l/r)aapa) 54 . As for the AIBs that we are focusing on in this study, they express at least inx-1 , which is selective for AIBs, and show a consistent number, location, and interneuron-like morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Few transient transcription factors affecting glial cell identity are described. Hmx/Nkx/MLS-2 and Pax6/VAB-3 drive Olig2/HLH-17 expression in CEPsh glia, similarly to their homologs driving Olig2 expression in mouse glia, Aristaless/ALR-1 regulates the functional structure of AMso glia, FOXD4/UNC-130 instructs specification of ILsoD, Atoh1/LIN-32 instructs diversification of AMsh glia, while Prox1/PROS-1 regulates the secretome of AMsh glia and OTX/OTD/TTX-1 their stressed-induced remodeling ( Tucker et al, 2005 ; Yoshimura et al, 2008 ; Procko et al, 2011 ; Wallace et al, 2016 ; Zhang et al, 2020 ; Mizeracka et al, 2021 ). Strikingly, these transcription factors regulating C. elegans glial fate also affect neuronal fates, alongside their glial functions ( Figure 4A ).…”
Section: Uncharted Terrains In Cell Types and Cell Heterogeneitymentioning
confidence: 99%
“…Recent C. elegans studies delineating transcription factor roles in convergent differentiation in neurons or glia may provide molecular insights in other species. FOXD4/UNC-130 is expressed in and required for the diversification of different cell types (neurons AWA, ASG, ASI and glia ILsoD) arising from the same sublineage but not the diversification of similar types arising from other sub-lineages ( Sarafi-Reinach and Sengupta, 2000 ; Mizeracka et al, 2021 ). On the other hand, Atoh1/LIN-32 is expressed in and required for the specification of related, left/right or radially symmetrical, neural cell types generated from distinct sublineages ( Masoudi et al, 2021 ).…”
Section: Exploring Cell Types Throughout Nervous System Developmentmentioning
confidence: 99%